2020
DOI: 10.3389/fmolb.2020.590018
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis Reveals the Distribution of Antibiotic Resistance Genes in a Large-Scale Population of Healthy Individuals and Patients With Varied Diseases

Abstract: The human gut microbiome is a reservoir for antibiotic resistance gene (ARG). Therefore, characterizing resistome distribution and potential disease markers can help manage antibiotics at the clinical level. While much population-level research has highlighted the strong effect of donor geographic origin on ARG prevalence in the human gut, little is known regarding the effects of other properties, such as age, sex, and disease. Here we employed 2,037 fecal metagenomes from 12 countries. By quantifying the know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Our results reveal that the common ARGs, detected in both IVF and tissue, confer multidrug resistance, as well as resistance to aminoglycosides, beta-lactams, and tetracycline antibiotics. A previous study showed that tetracycline, aminoglycoside, beta-lactam, MLS, vancomycin, and multidrug resistance genes are the dominant types in the human gut (Qiu et al, 2020). The human microbiome may constitute a mobilizable reservoir of ARGs, which are accessible to pathogenic bacteria for acquiring antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reveal that the common ARGs, detected in both IVF and tissue, confer multidrug resistance, as well as resistance to aminoglycosides, beta-lactams, and tetracycline antibiotics. A previous study showed that tetracycline, aminoglycoside, beta-lactam, MLS, vancomycin, and multidrug resistance genes are the dominant types in the human gut (Qiu et al, 2020). The human microbiome may constitute a mobilizable reservoir of ARGs, which are accessible to pathogenic bacteria for acquiring antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most ARGs in the human gut are those resistant to widely used antibiotics, and antibiotic therapy leads to personalized resistome diversification and individual-specific strain level selection in the gut microbiota (Li et al, 2019). Analysis of ARG distribution in the population provides an important indicator for public health policies (Qiu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 23 Diseases connected to gut inflammation have also been observed to lead to an expansion of the intestinal resistome, including type 2 diabetes, cirrhosis, obesity, and IBD. 7 , 24 , 57 A common mechanism of increased ARG prevalence across these diseases is likely the blooming of ARG-enriched taxa such as the Enterobacterales in response to a dysbiotic state. 58 Dietary and therapeutic interventions that reduce the abundance of Enterobacterales could therefore beneficially modulate the resistome.…”
Section: Environmental and Host Factors Shape The Gut Resistomementioning
confidence: 99%
“…Bacteria enriched in Ermf genes had resistance of macrolide, lincosamide, and streptogramin, while microbiota enriched in Vanug , Vanwg , and Vanrd had vancomycin resistance. The metagenomic analysis of antibiotic resistome in a large-scale healthy human demonstrated that Chinese population harbored the most abundant ARGs, and Ermf could be representative ARGs of the Chinese population ( Qiu et al., 2020 ). Except for antibiotics abuse, ARGs could be transferred horizontally through bacteria from food and animals, which means ARGs could be obtained through various ways such as the transmission of food chain ( Kumar et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%